Polymyalgia rheumatica mit und ohne Großgefäßvaskulitis - Schmidt, Wolfgang A. (DMW - Deutsche Medizinische Wochenschrift, 2020)
Polymyalgia rheumatica (PMR) is characterized by rapidly evolving shoulder and pelvic girdle pain with fatigue, weight loss, night sweats and elevated CRP and ESR. Giant cell arteritis (GCA) can occur in PMR and vice versa. Headache and scalp tenderness are typical for GCA. GCA may be complicated by visual loss or by strokes.Imaging, particularly ultrasound, is helpful for distinguishing PMR from similar conditions such as shoulder osteoarthritis, rheumatoid arthritis and chondrocalcinosis. Subdeltoid bursitis, biceps tenosynovitis and hip joint effusions are common in PMR. The diagnosis of GCA needs to be either confirmed by imaging or by histology. Ultrasound is the imaging method of choice provided that expertise and adequate equipment are available. Inflamed arteries exhibit a concentric wall thickening. Patients with extracranial GCA are younger, more often female. Vasculitis commonly involves the aorta, subclavian arteries, axillary arteries and other arteries. The diagnosis of extracranial GCA may be confirmed by ultrasound, CT, MRI or PET.Prednisolone with a starting dose of 15–25 mg/d for PMR and of 40–60 mg/d for GCA results in rapid improvement of symptoms. Fast-track clinics provide clinical and ultrasound examinations by experts within 24 hours. Their introduction led to a decrease of visual loss in GCA. The prednisolone dose can be discontinued within 1 year in about 50 % of GCA patients. Additional treatment with tocilizumab allows to reduce flares and decrease glucocorticoid doses. Tocilizumab is particularly useful in patients with relapses and with increased risk of glucocorticoid side effects.
Keywords: Riesenzellarteriitis; Polymyalgia rheumatica; Ultraschall; Bildgebung; Tocilizumab